2013
DOI: 10.1121/1.4816405
|View full text |Cite
|
Sign up to set email alerts
|

Hearing frequency thresholds of a harbor porpoise (Phocoena phocoena) temporarily affected by a continuous 1.5 kHz tone

Abstract: Harbor porpoises may suffer hearing loss when exposed to intense sounds. After exposure to a 1.5 kHz continuous tone without harmonics at a mean received sound pressure level of 154 dB re 1 μPa for 60 min (cumulative sound exposure level: 190 dB re 1 μPa(2) s), the temporary hearing threshold shift (TTS) of a porpoise was quantified at 1.5, 2, 4, 6.5, 8, 16, 32, 63, and 125 kHz with a psychoacoustic technique. Significant TTS only occurred at 1.5 and 2 kHz. Mean TTS (1-4 min after sound exposure stopped) was ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…02) had participated in previous psychoacoustic studies (Kastelein et al, 2010;Kastelein et al, 2012b;Kastelein et al, 2013b). During the present study, he was 7 yr old, his body mass was around 38 kg, his body length was 146 cm, and his girth at the axilla was approximately 75 cm.…”
Section: A Study Animal and Study Areamentioning
confidence: 98%
See 1 more Smart Citation
“…02) had participated in previous psychoacoustic studies (Kastelein et al, 2010;Kastelein et al, 2012b;Kastelein et al, 2013b). During the present study, he was 7 yr old, his body mass was around 38 kg, his body length was 146 cm, and his girth at the axilla was approximately 75 cm.…”
Section: A Study Animal and Study Areamentioning
confidence: 98%
“…Using a psychophysical technique, Kastelein et al (2012b) studied TTS in a harbor porpoise exposed to octave-band white noise centered at 4 kHz at several received SPLs and durations. Kastelein et al (2013b) showed that after a porpoise was exposed to a 1.5 kHz continuous tone without harmonics, TTS (1-4 min after sound exposure stopped) only occurred at 1.5 and 2 kHz hearing frequencies and concluded that low frequency sounds do not influence the hearing of harbor porpoises at the most ecologically important frequencies (i.e., those around 125 kHz, which is used for echolocation).…”
Section: Introductionmentioning
confidence: 98%
“…1. changes in the audiogram over a 3-4 year period (Kastelein et al, 2013). In this more recent study, the porpoise was not allowed to echolocate during research trials.…”
Section: Research Articlementioning
confidence: 99%
“…Based on this, PTS was predicted to occur for SEL values 15 dB above SEL, causing TTS onset (Southall et al, 2007). Recent measurements for continuous noise exposure and sonar sound suggest that the growth rates may well exceed 2.3 dB/dB in some cases (Kastelein et al, 2013(Kastelein et al, , 2014b. Given the lack of data on growth rates in harbour porpoises for impulsive sounds, let alone sound from explosions, the approach for extrapolating the TTS growth that is outlined by Southall et al (2007) was used.…”
Section: Risk Thresholds For Hearing Loss For Harbour Porpoises Exposmentioning
confidence: 99%
“…Harbour porpoises have sensitive hearing, making them potentially exceptionally vulnerable to noise-induced effects from anthropogenic sound-producing activities at sea (Culik et al, 2001;Kastelein et al, 2002Kastelein et al, , 2010Kastelein et al, , 2012aKastelein et al, , 2012bKastelein et al, , 2013Kastelein et al, , 2014aKastelein et al, , 2014bKastelein et al, , 2015aKastelein et al, , 2015bKetten, 2004;Lucke et al, 2009;Tougaard et al, 2009). The main potential effects of concern of underwater explosions on an individual animal are (1) trauma (from direct or indirect blast wave effect injury) such as crushing, fracturing, hemorrhages, and rupture of body tissues caused by the blast wave, resulting in immediate or eventual mortality; (2) auditory impairment (from exposure to the acoustic wave), resulting in a temporary or permanent hearing loss such as temporary threshold shift (TTS) and permanent threshold shift (PTS); or (3) behavioural change, such as disturbance to feeding, mating, breeding, and resting.…”
Section: Introductionmentioning
confidence: 99%